More Problems on Linear Systems and Matrices


\begin{displaymath}B = \left(\begin{array}{rrrr}
a & b \\
c & d\\
\end{array} \right) \;.\end{displaymath}

Then we have

\begin{displaymath}A\; B = \left(\begin{array}{rrrr}
a-c & b-d \\
2a+c &2b+d\\
\end{array} \right) \end{displaymath}


\begin{displaymath}B\; A = \left(\begin{array}{rrrr}
a+2b & -a+b \\
c+2d &-c+d\\
\end{array} \right) \;.\end{displaymath}

So the equation $A\;B = B\; A$ implies

a-c &=& a+2b \\
b-d &=& -a+b \\
2a+c &=& c+2d \\
2b+d &=& -c+d \\
\end{array} \right.\end{displaymath}

This clearly implies

\begin{displaymath}c = -2b \;\;\mbox{and}\;\; a=d\end{displaymath}


\begin{displaymath}B = \left(\begin{array}{rrrr}
a & b \\
-2b & a\\
\end{array} \right) \end{displaymath}

where $a$ and $b$ are two arbitrary numbers. Consider the matrix

\begin{displaymath}C = \left(\begin{array}{rrrr}
1 & 1 \\
1 & 1\\
\end{array} \right)\;.\end{displaymath}

Since $C$ is not of the form found before, then we must have

\begin{displaymath}A\;C \neq C\; A\;.\end{displaymath}

The reader may want to check that is the case.

Click on Next Problem below to go to the next problem.

[Next Problem] [Matrix Algebra]
[Trigonometry] [Calculus]
[Geometry] [Algebra] [Differential Equations]
[Calculus] [Complex Variables]

S.O.S MATHematics home page

Do you need more help? Please post your question on our S.O.S. Mathematics CyberBoard.

Mohamed A. Khamsi

Copyright 1999-2019 MathMedics, LLC. All rights reserved.
Contact us
Math Medics, LLC. - P.O. Box 12395 - El Paso TX 79913 - USA
users online during the last hour